Work Family Conflict Relationship to Organizational Commitment with Perceived Organizational Support as a Mediation Variable at Puri Husada Hospital Tembilahan - Irka Srinofita; Ririn Handayani; Fahmi Oemar (SAINS ORGANISASI, 2022)
The hospital as one of the health care facilities in general has a very important role in efforts to raise the level of public health. This study aims to see how the organizational commitment of hospital employees is seen from work conflict and organizational support. This type of research is explanatory research. The population is the employees of Puri Husada Tembilahan Hospital, amounting to 49 people. Data analysis in this study using SEM-PLS. Based on data processing, it was found that social support mediates the effect of work-family conflict on organizational commitment. The test results show that there is a significant influence of family work conflict mediating social support on organizational commitment, thus, it can be concluded that social support can act as a mediating variable for medical personnel at Puri Husada Tembilahan Hospital.